The Ramification of Prestigious Underwriters, IPO Pricing Method, and Institutional Allocation on Indonesia IPO Underpricing during 2010-2021 - Sembiring, Jossmelkr; Sukamulja, Sukmawati (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
This research analyses how prestigious underwriters, IPO pricing, and share allocations shape IPO underpricing in Indonesia. 359 out of 406 Indonesian companies in the period 2010-2021 were underpriced on the first day of trading, noting the importance of investigating the rationale behind the underpricing phenomenon, which proliferates in the finance literature. This study examines the degree of IPO underpricing after the period post-Global Financial Crisis and the outbreak of COVID-19. This research found that the mean of underpricing amounted to 36,77% in 2010-2021. Prestigious underwriters have been proven significantly squeeze the level of underpricing vis-à-vis non-prestigious underwriters. Moreover, the research found that most institutional investors get disproportionately higher shares of the issuing companies. The finding signifies the lucrative capital gain for investors to pursue on the first day of trading.